Basic Intonation Patterns of Galician Spanish - Pérez Castillejo, Susana; de la Fuente Iglesias, Mónica (Languages (Basel), 2024)
This paper presents an inventory of pitch accents and boundary tones in Galician Spanish (GS), a variety spoken in Northwestern Spain. Research so far has focused on explaining GS intonation features as transfer phenomena from Galician, the vernacular Romance language in the region. Because of this, previous studies have often included Galician L1 speakers, for whom transfer is expected when speaking Spanish L2. However, GS is the single L1 of half the children in Galicia, and it is spoken almost exclusively by about a quarter of Galicians. Our study focuses on this population and investigates the relative frequency and distribution of tonal units in GS when direct transfer from Galician is unlikely. A corpus of 1706 sentences (statements, questions, imperatives, and vocatives in neutral and biased contexts) was obtained from 28 participants through a discourse completion task. Results showed that patterns previously attributed to direct transfer from Galician L1 (for example, upstepped final accents in neutral declaratives or falling contours in unmarked interrogatives) are widespread in GS as L1. Findings also show commonalities with other L1 Spanish varieties, both in Europe (for example, L* L% as the unmarked declarative ending) and America (for example, the L* + H prenuclear accent of Caribbean varieties).